Observatories in Malaysia: Descendants of islamic civilization superiority - Ibrahim I.A.; Safiai M.H.; Jamsari E.A.; Ahmad M.Y.; Amir Husin Mohd Nor; Nasir B.M.; Hehsan A. (IAEME Publication, 2024)
Indexed by Scopus